PENGARUH INFORMASI KEUANGAN, NON KEUANGAN DAN EKONOMI MAKRO TERHADAP UNDERPRICING PADA PERUSAHAAN YANG MELAKUKAN INITIAL PUBLIC OFFERING (IPO) PERIODE 2011 – 2013 DI BURSA EFEK ONDONESIA - Altensy, Mica; Agusti, Restu; -, Rofika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to examine the variables that influence of underpricing stock price when the company's initial public offering in Indonesia Stock Exchange 2011 - 2013 period. The dependent variable in this study is underpricing measured by value of initial returns, while the independent variable is the financial leverage, return on equity, proceeds underwriter reputation, auditor reputation, firm age, inflation, BI rate. The data used in this study is a secondary data that collected by using purposive sampling method. Sample of 45 companies from 77 populations companies doing IPOs from 2011 - 2013 in Indonesia Stock Exchange. This study used multiple regression for data analysis. The results of this study showed that the variable underwriter reputation and auditor reputation negatively influence of underpricing is proven. Other variables such as financial leverage, return on equity, proceeds, firm age, inflation, and BI rate influence of underpricing is not proven. In this research model, shows the variable financial leverage, return on equity, proceeds, underwriter reputation, auditor reputation, firm age, inflation, and BI rate can only explain the variation of underpricing of 32.4 %.Keywords: Financial Information, Non Financial, Macro Economy, and Under-pricing.